Tunable three dimensional scaffolds for tissue engineering applications - Loh, Qiu Li. (2013)
Three-dimensional (3D) cultures have become increasingly significant and promising tools in tissue engineering applications. Hence, 3D scaffolds that are typically porous, biocompatible and biodegradable materials have been widely studied for the replacement or repair of damaged tissues and organs. Although the use of 3D scaffolds for biomedical applications is increasingly common, the study of 3D scaffolds with tunable properties post-fabrication has been limited. The development of such tunable scaffolds will enable precise modification and tailoring of scaffolds post-fabrication to suit the needs of various applications. Therefore, the feasibility of tuning the properties of alginate scaffolds post-fabrication and the ability of these scaffolds in directing cellular behaviour was investigated in this study. The 3D alginate scaffolds were tuned so as to alter the final properties e.g. stiffness or porosity, which have direct implications on cellular behaviour as the cells are capable of sensing mechanical cues from their immediate 3D microenvironment. Detailed bulk and surface material characterization studies combined with cellular and molecular studies were carried out so as to investigate the role of different material properties on cellular behavior in a 3D microenvironment. Subsequently, novel tunable alginate scaffold fabrication methods were investigated to contribute to current efforts directed at the development of cell-instructive scaffolds. Overall, the current study provides new insights into the role of the 3D physical environment in determining cellular function, and is a stepping stone towards the development of instructive scaffolds with tunable properties post-fabrication for tissue engineering applications.